Discontinuation rates following a switch from a reference to a biosimilar biologic in patients with inflammatory bowel disease: A systematic review and meta-analysis - Queiroz, Natália Sousa Freitas; Saad-Hossne, Rogerio [UNESP]; Fróes, Renata de Sá Brito; Penna, Francisco Guilherme Cancela E.; Gabriel, Stefania Burjack; Martins, Adalberta Lima; Teixeira, Fabio Vieira (FapUNIFESP (SciELO), 2020)
– Background – Biologics have revolutionized the treatment of inflammatory bowel disease (IBD). However, these drugs had a significant influence on treatment-related costs, which resulted in the development of biosimilars. Objective – This systematic review and meta-analysis aimed to evaluate the drug discontinuation rate in the IBD population who switched from originator to biosimilars in real-world switching studies and address potential nocebo effects as reasons for drug discontinuation. Methods – Medline (via PubMed), EMBASE, Cochrane Library, and abstract databases of selected congresses were screened for reports of monoclonal antibody (mAb) switching with a minimum post-switch follow-up of >6 months or three infusions. All available information on discontinuation rates was assessed. Results – A total of 30 observational studies were included, involving 3,594 patients with IBD. Twenty-six studies reported a switch from infliximab to CT-P13, two studies involved a switch to SB2, and switching information was not available in two studies. The discontinuation rates were 8%, 14%, and 21% at 6, 12, and 24 months, respectively. The main reasons for drug discontinuation and their respective risks were: disease worsening (2%), remission (4%), loss of adherence (4%), adverse events (5%), and loss of response (7%). The quality of the evidence ranged from low to very low depending on the outcome analyzed. Subjective symptoms leading to drug discontinuation were infrequently reported, and the nocebo effect was clearly assessed in just one of the included papers. Conclusion – Discontinuation rates following a switch to a biosimilar in patients with IBD increase over time. However, it was not possible to confirm the nocebo effect as a reason for discontinuation. Therefore, long-term studies evaluating the use of biosimilars to monitor adverse events and potential nocebo effects in post-marketing surveillance are still needed.
Taxas de descontinuação do tratamento após a troca de um biológico originador por um biossimilar em pacientes com doenças inflamatórias intestinais: Revisão sistemática e metanálise.
Keywords: Biological products; Biosimilar pharmaceuticals; Inflammatory bowel diseases, drug therapy; Review; Therapeutic equivalency